Differences in expertise and values: Comparing community and expert assessments of a transportation project. (January 2017) - Nadafianshahamabadi, Razieh; Tayarani, Mohammad; Rowangould, Gregory M.
Highlights: Compare expert and community based MCDA of a transportation project. Experts and community members reach very different conclusions. Differences in expertise and values likely explain differences. Community member values and expert knowledge should be combined. Abstract: Transportation projects contain many tradeoffs between environmental, social, and economic benefits and costs that affect different groups of stakeholders, each with different priorities and values. Transportation project sponsors are therefore faced with an incredibly difficult decision making task. Multi-criteria decision analysis (MCDA) provides a flexible framework for considering a wide array of potential impacts that may be used as a supplement of substitute for cost benefit analysis or unstructured decision making. In this study, we evaluate the outcome of two MCDAs, one conducted with input from technical experts and the other with input from a sample of community members for a proposed highway project in Tehran, Iran. We explore how various criteria now commonly considered in urban transportation projects are viewed by these two groups that differ in their technical expertise and values. We find that experts score the project poorly while the community scores it favorably. The results demonstrate that the outcome of seemingly objective analysis tools commonly used in the transportation field depends on who provides critical technical assessments and value judgments and therefore the importance of community involvement.